Revisiting the 2006 School Level Curriculum and the Genre-based Approach in the Context of EFL Curriculum Development in Indonesia - Ahmad Budairi (Ahmad Dahlan Journal of English Studies, 2015)
AbstractThe genre-based approach has been known to characterize pedagogical practices during the implementation of the 2006 school-level curriculum.  Despite its prevalent use and overwhelming support by school stakeholders,  the efficacy of this approach was nonetheless questionable. This paper aims to revisit the 2006 School level curriculum, its plausibility and compatibality with individual contexts and its bearing on EFL practices. It also disusses the Genre-based approach in terms of  its  underlying paradigms, and  possible variables and contextual factors which might have impinged on its implementation. Some research findings on the adoption of the approach in Southeast Asia context are also presented to provide insights into how the Genre-based approach could be efficiently adopted. This essay concludes with some ideas for the amendment to  the 2006 school- level curriculum and how the genre-based approach might still be relevant in the context of teaching writing skills at tertiary education.